2019
DOI: 10.3389/fnagi.2018.00428
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Alleviates Cognitive Deficits and β-Amyloid Accumulation in APP/PS1 Mouse Model Via Activation of the cAMP/PKA/CREB/BDNF Pathway and Inhibition of Neuronal Apoptosis

Abstract: Alzheimer’s disease (AD) is characterized clinically by progressive cognitive decline and pathologically by the accumulation of amyloid-β (Aβ) in the brain. Royal jelly (RJ), a secretion of honeybee hypopharyngeal and mandibular glands, has previously been shown to have anti-aging and neuromodulatory activities. In this study, we discovered that 3 months of RJ treatment substantially ameliorated behavioral deficits of APP/PS1 mice in the Morris Water Maze (MWM) test and step-down passive avoidance test. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 55 publications
(56 reference statements)
1
31
0
1
Order By: Relevance
“…More, PD is known as manifest Lewy body dementia because severe cognitive alterations develop, especially during late stages of the disease [ 19 ]. Research shows that propolis and RJ possess a capacity to improve cognitive performance [ 71 ] and alleviate depressive symptoms through mitigation of oxidative stress [ 117 ] and activation of signaling pathways that promote the production of various neurotrophic factors such as BDNF [ 118 ], GDNF [ 102 ], and NGF [ 119 , 120 ]. Altogether, according to these scenarios, propolis and RJ may represent a multidimensional treatment, which may promote the quality of life among PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…More, PD is known as manifest Lewy body dementia because severe cognitive alterations develop, especially during late stages of the disease [ 19 ]. Research shows that propolis and RJ possess a capacity to improve cognitive performance [ 71 ] and alleviate depressive symptoms through mitigation of oxidative stress [ 117 ] and activation of signaling pathways that promote the production of various neurotrophic factors such as BDNF [ 118 ], GDNF [ 102 ], and NGF [ 119 , 120 ]. Altogether, according to these scenarios, propolis and RJ may represent a multidimensional treatment, which may promote the quality of life among PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that overexpression of hTau in hippocampal neurons pronouncedly impaired PKA signaling in both total lysates and the nuclear fraction compared with the vector control. The role of PKA on memory maintenance in different brain subset and pathologies is not always consistent, some researchers show that Aβ inhibits PKA, while activating PKA in hippocampus can improve cognitive functions (Gong et al, ; You et al, ). Other studies show that PKA accelerates tau phosphorylation, while inhibiting PKA in the prefrontal cortex improves memory in both aged rats and monkeys (Wang et al, ; Xie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairment and depression-like behaviors in ovariectomized rats are recovered to the levels of sham-operated rats by RJ administration [171]. RJ administration has the potential to consolidate the learning, memory abilities, and longevity of honeybees [112], and the intake of RJ has the potential to ameliorate cognitive deficits [103]. RJ ingestion is effective on neurological disorders, such as Alzheimer's disease in postmenopausal patients, via decreasing cholesterol and amyloid-beta deposition, increasing cholinergic response, estrogen level, and also improving the blood-brain barrier and autonomic nervous systems [102].…”
Section: Neuroprotective Effectmentioning
confidence: 99%